Renewable energy can drive job creation in the GCC - Ferroukhi, R; Khalid, A (Oxford Institute for Energy Studies, 2015)
As global economies continue to struggle with remnants of the persistent economic crisis, unemployment and its associated social and economic impacts remains a key concern and an instrumental driver of public policy